School-related Variables Support toward the Utilization of Language Learning Strategies in a Private Bilingual High School - Anis Etikasari; Ikmi Nur Oktavianti; Badli Esham Ahmad (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
Learning strategies play significant roles in successful English language learning, especially in the EFL context where inputs are limited. However, the use of learning strategies is highly affected by internal variables, e.g., motivation, learning style, and external variables, e.g., school-related variables. This study aims at exploring the roles of school-related variables in supporting the use of language learning strategies. This study was conducted in a private bilingual high school in Yogyakarta, Indonesia, and five students who fulfilled the criteria were selected as the participants. The data were collected through semi-structured online interviews and recorded for more accessible analysis. The results of the interview were then analyzed using thematic analysis. The results of the study showed that school-related variables have significant and distinctive roles in supporting the use of language learning strategies. Each variable has its parts, e.g., the curriculum deals with language input, and the learning environment can enhance students’ motivation. Thus, teachers and school principals should be aware of their prominent roles and be able to design and create supportive school-related variables for their students.